Perbandingan Pengaruh Air Gambut Dan Air Hujan Terhadap Asphalt Concrete – Wearing Course (AC-WC) - Harpian Surya; Alfian Malik; Yosi Alwinda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The road pavement that was inundated by peat water would be easily damaged since asphalt is quickly oxidized by acid in peat water. This damage could also occurred due to inundated by rain. The road pavement submerged by rainwater will make aggregate and asphalt easily separated. This study aims to determine the impact of peat water and rain on the characteristic of AC-WC asphalt through Marshall tests using asphalt penetration 60/70. The tests were carried out using the Marshall tests based on the Indonesian Standard from Bina Marga 2018. The specimens were soaked for 24, 48, 72, and 96 hours in the temperature of 60°C. The tests results shows that immersion in the peat water and rain could decreased the stability of asphalt value as soaking time increased. Based on the results, it is shown that the asphalt has stability values of 1103.68 kg, 948.81 kg, 854.48 kg, and 780.55 kg, respectively, after soaked in peat water for 24, 48, 72, 96 hours. Also, it is shown that the asphalt has stability values of 1206.43 kg, 1185.68 kg, 978.94 kg, dan 889.85 kg, respectively, after soaked in rain water for 24, 48, 72, 96 hours. In peat water, the asphalt has RSI value of 95.83%, 82.38%, 74.19%, 67.77%, respectively, after soaked for 24, 48, 72, 96 hours and in rain water, the asphalt has RSI value of 97.18%, 95.51%, 78.85%, 71.68%, respectively, after soaked for 24, 48, 72, and 96 hours. It was obtained that asphalt soaked in rain water has a better RSI value than asphalt soaked in peat water and it is complied with the requirement of Bina Marga 2018 (90%).Keywords: Rain, peat water, AC-WC